Paleobotanical proxies for early Eocene climates and ecosystems in northern North America from middle to high latitudes - C. K. West; D. R. Greenwood; T. Reichgelt; A. J. Lowe; J. M. Vachon; J. F. Basinger (Climate of the Past, 2020)
Early Eocene climates were globally warm, with ice-free conditions at both poles. Early Eocene polar landmasses supported extensive forest ecosystems of a primarily temperate biota but also with abundant thermophilic elements, such as crocodilians, and mesothermic taxodioid conifers and angiosperms. The globally warm early Eocene was punctuated by geologically brief hyperthermals such as the Paleocene–Eocene Thermal Maximum (PETM), culminating in the Early Eocene Climatic Optimum (EECO), during which the range of thermophilic plants such as palms extended into the Arctic. Climate models have struggled to reproduce early Eocene Arctic warm winters and high precipitation, with models invoking a variety of mechanisms, from atmospheric CO 2 levels that are unsupported by proxy evidence to the role of an enhanced hydrological cycle, to reproduce winters that experienced no direct solar energy input yet remained wet and above freezing. Here, we provide new estimates of climate and compile existing paleobotanical proxy data for upland and lowland midlatitude sites in British Columbia, Canada, and northern Washington, USA, and from high-latitude lowland sites in Alaska and the Canadian Arctic to compare climatic regimes between the middle and high latitudes of the early Eocene – spanning the PETM to the EECO – in the northern half of North America. In addition, these data are used to reevaluate the latitudinal temperature gradient in North America during the early Eocene and to provide refined biome interpretations of these ancient forests based on climate and physiognomic data.